2017
DOI: 10.1016/j.jrp.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing types of social withdrawal in children: Internalizing and externalizing outcomes of conflicted shyness versus social disinterest across childhood

Abstract: Little research has examined the effect of subtypes of social withdrawal on the development of psychopathology across childhood. Parents of 493 children (220 females) completed a measure of their child’s conflicted shyness and social disinterest as well as the Child Behaviour Checklist (CBCL) when their child was age 3, and again at age 6. When children were age 9, parents completed the CBCL. From 3 to 6, conflicted shyness predicted increases in anxiety symptoms in boys and girls, and predicted depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 48 publications
3
41
2
1
Order By: Relevance
“…The term shyness shares conceptual overlap with a number of other similar constructs (e.g., behavioral inhibition, Kagan, 1997; anxious solitude, Gazelle & Ladd, 2003). Even in early childhood, shyness is concurrently and predictively associated with socioemotional difficulties, including peer problems (e.g., deficits in social skills, peer rejection, victimization) and internalizing difficulties (e.g., social anxiety, loneliness) (Bohlin, Hagekull, & Andersson, 2005;Coplan, Arbeau, & Armer, 2008;Karevold, Ystrøm, Coplan, Sanson, & Mathiesen, 2012;Kopala-Sibley & Klein, 2017).…”
Section: Multiple Forms Of Social Withdrawal In Early Childhoodmentioning
confidence: 99%
See 2 more Smart Citations
“…The term shyness shares conceptual overlap with a number of other similar constructs (e.g., behavioral inhibition, Kagan, 1997; anxious solitude, Gazelle & Ladd, 2003). Even in early childhood, shyness is concurrently and predictively associated with socioemotional difficulties, including peer problems (e.g., deficits in social skills, peer rejection, victimization) and internalizing difficulties (e.g., social anxiety, loneliness) (Bohlin, Hagekull, & Andersson, 2005;Coplan, Arbeau, & Armer, 2008;Karevold, Ystrøm, Coplan, Sanson, & Mathiesen, 2012;Kopala-Sibley & Klein, 2017).…”
Section: Multiple Forms Of Social Withdrawal In Early Childhoodmentioning
confidence: 99%
“…The child social preference scale (CSPS, Coplan et al, 2004) was developed as a parental rating scale to specifically distinguish between shyness and unsociability in young children. It has good psychometric properties across multiple samples (e.g., Coplan & Weeks, 2010;Kopala-Sibley & Klein, 2017) and has been successfully translated for use in other cultures (e.g., China; Li et al, 2016;Japan;Okada, Tani, Ohnishi, Nakajima, & Tsujii, 2012). In the present study, we created a new subscale for the CSPS, designed specifically to assess social avoidance (renamed the CSPS-3 to reflect the addition of a third subscale).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, research in North America found that shy preschoolers frequently opt to play alone in the presence of peers and, consequently, may be more excluded by peers (Coplan, Ooi, Rose‐Krasnor, & Nocita, ; Ooi, Baldwin, Coplan, & Rose‐Krasnor, ). Shy preschoolers also tend to display more internalizing problems, such as anxious‐withdrawn behaviors and depressive symptoms (Coplan, Ooi, Xiao, & Rose‐Krasnor, ; Kopala‐Sibley & Klein, ; Sette, Zava, Baumgartner, Baiocco, & Coplan, ). Furthermore, shyness (behavioral inhibition) is a risk factor for later social anxiety disorder (Clauss & Blackford, ), and stable, increasing levels of shyness in a longitudinal study of Norwegian children were found to predict symptoms of anxiety and depression in adolescence (Karevold, Ystrøm, Coplan, Sanson, & Mathiesen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In partial support of this model, Kopala-Sibley and Klein (2017) reported that unsociability at age 3 was not associated with concurrent or subsequent internalizing (depressive symptoms, anxiety symptoms) or externalizing difficulties at ages 6 and 9…”
Section: Unsociabilitymentioning
confidence: 91%